Nopol synthesis from β-pinene and turpentine oil over Sn-MCM-41 - Edwin Alexis Alarcón Durango; Aída Luz Villa Correa; Consuelo Montes de Correa (Revista Facultad de Ingeniería Universidad de Antioquia, 2006)
Nopol was obtained by the Prins condensation of β-pinene and paraformaldehyde over Sn-MCM-41. The catalyst was synthesized by chemical vapor deposition using a Sn salt over MCM-41. Reactions were carried out using either high purity β-pinene or turpentine oil as a starting material. The effect of catalyst Sn loading, temperature, type of solvent, catalyst amount, and reaction time on nopol selectivity was studied. Catalyst samples were characterized by XRD, IR, UV-VIS, elemental analysis and BET surface area. Low Sn loaded Sn-MCM-41 yields near 100% nopol with high purity β-pinene; whereas using turpentine as β-pinene source, nopol selectivities up to 93% were attained for equimolar ratios of reactants.